Working with coaches and their teams in youth and collegiate sport in the USA: Commentary - Crudgington, B.; Mallett, C. J. (International Journal of Sports Science & Coaching, 2018)
The dialogue between Andy and Simon reminds us that coaching and working with coaches, especially in (high) performance contexts, are highly relational and contested, and therefore understandably complex and uncertain. These vignettes can be useful for coach developers, coaches, and consultants to reflect upon in terms of their own experiences in and through their work; therefore, we are grateful for the opportunity of the ideas and themes within these vignettes. Andy describes his own related experiences; initially as an athlete, then as a coach, a strength and conditioning consultant, followed by doctoral studies related to examining and understanding behavior in sport. We note that his development has been underpinned by a number of personal observations on poor coaching practice, and this background is useful in understanding Andy`s approach to these varied situations.